2015
DOI: 10.1002/zoo.21257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in human health parameters associated with a touch tank experience at a zoological institution

Abstract: Association of Zoos and Aquariums (AZA) institutions provide a variety of benefits to visitors. However, one area that has received little study is the direct human health benefits from zoo and aquarium visits. With the increase in stress related non-infectious diseases in industrialized countries, understanding the extent of these benefits is important. We studied the effects on visitor stress of an experience at a touch tank exhibit featuring stingrays, sharks, and horseshoe crabs. Stress was measured by phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…In one study, a single zoo visit was shown to decrease blood pressure and result in approximately 6000 steps walked per visit [20]. In another study, visitors interacting with stingrays in a touch tank at a zoo felt happier, more energized, and less tense after their visit [21]. The impact that zoo visits have on human health and well-being are still poorly understood, but warrant further study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, a single zoo visit was shown to decrease blood pressure and result in approximately 6000 steps walked per visit [20]. In another study, visitors interacting with stingrays in a touch tank at a zoo felt happier, more energized, and less tense after their visit [21]. The impact that zoo visits have on human health and well-being are still poorly understood, but warrant further study.…”
mentioning
confidence: 99%
“…The impact that zoo visits have on human health and well-being are still poorly understood, but warrant further study. Engagement with the outdoors provides humans with psychological, emotional, spiritual and even physical benefits and it is thus imperative that we also understand how zoos impact human health [20], [21], [22], [23], [24], [25], [26], [27].…”
mentioning
confidence: 99%
“…A further interesting insight into the potential for nature interaction to reduce cortisol is via the subjective contextual elements of the specific interaction—captured here as number of lemurs seen and lemur proximity, both of which were positively related to outcomes. Previous studies have shown improvements in parameters of health after explicit, active interaction with non‐companion animals (Sahrmann et al, ), but none have yet explored a passive animal‐led interaction. An important part of biophilic response is said to be related to feelings of awe or privilege in nature interactions (Orr, ), the latter concept being something particularly evocative when animal encounters are unpredictable and not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in blood pressure (both systolic and diastolic) were reported among zoo visitors (Sakagami & Ohta, ); however, as the content of the zoo experience was not studied, the drivers of this decrease could not be ascertained. More specifically, Sahrmann, Niedbalski, Bradshaw, Johnson, and Deem () found that heart rate dropped significantly and mood improved, which both suggest a decrease in stress, after touch tank experiences.…”
Section: Introductionmentioning
confidence: 99%
“…44 Despite the popularity of touch tanks, there is a paucity of research about animal health in these 45 exhibits. The few studies focusing on elasmobranchs in and associated with touch tanks 46 examined shark growth rates (Payne and Rufo 2012), plasma biochemistry values (Persky et al 47 2012), goiter onset (Morris et al 2012), stingray abscess development (Clarke III et al 2013), 48 behavior (Casamitjana 2004), as well as the human stress response and emotional responses to 49 contact with the animals (Sahrmann et al 2015). Casamitjana (2004) suggested that touch tank 50 exhibits may be maladaptive to elasmobranchs and other studies reported that abnormalities are 51 occasionally observed (Persky et al 2012; Morris et al 2012).…”
mentioning
confidence: 99%